2021
DOI: 10.1039/d1tc04366h
|View full text |Cite
|
Sign up to set email alerts
|

Organic-semiconductor nanoarchitectonics for multi-valued logic circuits with ideal transfer characteristics

Abstract: We introduce a rational design approach to high-performance multi-valued logic circuits. Taking an organic-based ternary inverter as a model system, robust input parameters to a two-dimensional finite-element solver are estimated....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Their study showed that the temperature dependencies of the V peak and I peak were consistent with those of the threshold voltages. The thickness of the semiconductor film also influences the threshold voltage, as demonstrated by Jo et al , 34 who performed two-dimensional finite-element simulations to systematically investigate the impact of film thickness on the threshold voltage. They noted that channel thickness must be optimized to improve device performance.…”
Section: Fundamentals Of Antiambipolar Transistorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Their study showed that the temperature dependencies of the V peak and I peak were consistent with those of the threshold voltages. The thickness of the semiconductor film also influences the threshold voltage, as demonstrated by Jo et al , 34 who performed two-dimensional finite-element simulations to systematically investigate the impact of film thickness on the threshold voltage. They noted that channel thickness must be optimized to improve device performance.…”
Section: Fundamentals Of Antiambipolar Transistorsmentioning
confidence: 98%
“…Other influential parameters on the AAT properties are the channel lengths (L p and L n for the p-and n-channels, respectively), and the ratio of L p /L n . 34,35 Especially as the lateral distribution of the applied V D is determined by these length parameters, the carrier accumulation and depletion in each semiconductor region are strongly affected. In fact, experimental data has confirmed that an optimized L p /L n increased I peak and reduced V peak .…”
Section: Materials Advances Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an experimental screening and prioritization of these factors can generally be a demanding task. To solve this issue, recent studies have employed a multiparameteric simulation and modeling approach to provide both fundamental insights and practical engineering guidelines for OHTs and related systems. If we take it one step further, it might become even possible that totally new materials combinations and device concepts are predicted from simulation, enabling sharply focused research for new applications.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…However, the carrier-transport mechanism remains unclear although the transport has been explained in analogy with a shoot-through current (STC) in a CMOS inverter. [18][19][20][21][22][23][24][25] Thus, revealing the carrier-transport mechanism is a critical issue to clarify the origin of the NDT and improve the device's performance. Herein, we use operando photoemission electron microscopy (PEEM) to tackle this issue.…”
Section: Introductionmentioning
confidence: 99%